Campaign to Introduce Children Yoga to the Mothers in Bandung City - Nyolinda, Vilna Agus; Hartanti, Monica (VCD: Journal of Visual Communication Design, 2016)
Childhood is the time when a person grows rapidly. Unfortunately, children nowadays watch too much television that they do not exercise enough. As a result, they do not grow as rapidly as they are supposed to, such as their bone and muscle growth as well as their sensory and motoric nerve and their ability to concentrate. Yoga for children is an exercise with many benefits for children’s physical and mental growth. Therefore, this social campaign was created to introduce yoga for children towards mothers in the city of Bandung to invite them into doing yoga at home with their children as a routine. The design method used in this campaign is using visual style of “Children Visual Language and Children Drawing” with event as its main media and supporting medias such as: poster, flyer, magazine, website, social media, gadget application and gimmicks. The aim of this campaign design is promoting healthy growth and development for children after they do yoga for children along with their mothers.